Pancasila Education in Indonesia: The debate on Pancasila in the post reform era between legitimation, recognition, and institutionalization during 2000-2021 - Hastangka, Hastangka; Ediyono, Suryo (Universitas Negeri Yogyakarta, 2023)
Pancasila is mentioned as the basis of the philosophy of the State. Understanding the narrow and limited meaning of Pancasila has resulted in polemics in the life of the nation and state, especially in Pancasila education. This study aims to analyze the debate and dynamics of Pancasila education from the aspects of legitimacy, recognition, and institutionalization. This research is philosophical research, using qualitative research methods through literature review. The analysis in this study used critical discourse analysis. The research process includes data inventory, data categorization, and data analysis. The results of this study indicate that the debate about Pancasila education since the post occurred from the framework of the legitimacy of power, there has been a dualism of legitimacy between the executive and the legislature. Based on the recognition aspect, Pancasila education has not yet received adequate recognition from the state and educational institutions. From the institutional aspect, efforts to institutionalize the values of Pancasila from the educational aspect still encounter problems because there is no certainty in placing Pancasila under what kind of institution.